Impact of nutritional and sanitary management on Apis mellifera colony dynamics and pathogen loads - Giacobino, Agostina; Pacini, Adriana; Molineri, Ana; Bulacio-Cagnolo, Natalia; Merke, Julieta; Orellano, Emanuel; Gaggiotii, Mónica; Signorini, Marcelo (Spanish Journal of Agricultural Research, 2022)
Aim of study: The aim of this study was to assess the impact of the mite control strategies combined with nutritional management on honey bee colony dynamics and survival during winter, the following spring, and summer.Area of study: Santa Fe province in central Argentina.Material and methods: We set two apiaries with 40 colonies each and fed one apiary with high fructose corn syrup (HFCS) and the other with sucrose syrup (SS). Within each apiary, we treated half the colonies against Varroa mites and half of these treated colonies also received a pollen patty.  The other half of the colonies remained untreated and did not received pollen patties. All colonies were sampled for Varroa infestation level, Nosema ceranae abundance and colony strength seven times during a year (from summer 2016 to autumn 2017). We computed autumn mite invasion and colony losses at each sampling time.Main results: Colonies fed with HFCS had more brood cells during the study that those fed with SS and treated colonies had fewer adult bees and Varroa infestation than untreated colonies. No significant effect of the protein supplementation was observed on any of the response variables. , SS colonies from all groups had significantly more mites drop counts than HFCS colonies.Research highlights: Considering that a reduced frequency of application is desirable, our results suggested that nutrition management could enhance chemical treatment effectiveness since honey bees might profit from improved nutrition. However, a better understanding of the nutritional requirements of the colonies under field conditions is needed.